Accounting information systems - Romney, Marshall B. (Pearson, 2015)
This market-leading text delivers the most comprehensive and flexible coverage of the our major approaches to teaching AIS, while allowing instructors the flexibility to reorder chapters and focus the material to suit their individual course needs. This new edition has been updated to cover all of the most recent developments in AIS and to show AIS has changed the roles of an accountant